2015
DOI: 10.1063/1.4929368
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced changes in the electron density distribution in α-Ge near the α-β transition

Abstract: Electron density distributions in aGe have been determined under high pressure using maximum entropy method with structure factors obtained from single crystal synchrotron x-ray diffraction in a diamond anvil cell. The results show that the sp 3 bonding is enhanced with increasing pressure up to 7.7(1) GPa. At higher pressures but below the a-b transition pressure of 11.0(1) GPa, the sp 3-like electron distribution progressively weakens with a concomitant increase of d-orbitals hybridization. The participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 39 publications
(42 reference statements)
2
27
0
Order By: Relevance
“…Apparently, the multigrain approach is an effective way to increase redundancy and completeness in data collection, thus significantly improving the HP singlecrystal data quality. HP multigrain XRD possesses great potential for the crystallographic studies of materials under HP, as demonstrated recently in studies of crystal structural determination of (Mg,Fe)SiO3 bridgmanite [194], post-bridgmanite [166], SiO2 [167], and -Ge [102].…”
Section: Hp Multiple Grain Xrdmentioning
confidence: 99%
See 4 more Smart Citations
“…Apparently, the multigrain approach is an effective way to increase redundancy and completeness in data collection, thus significantly improving the HP singlecrystal data quality. HP multigrain XRD possesses great potential for the crystallographic studies of materials under HP, as demonstrated recently in studies of crystal structural determination of (Mg,Fe)SiO3 bridgmanite [194], post-bridgmanite [166], SiO2 [167], and -Ge [102].…”
Section: Hp Multiple Grain Xrdmentioning
confidence: 99%
“…HP multigrain crystallography has been recently developed for single-crystal structure determination [151], which is particularly useful for studying the structural properties of phases that are not recoverable at ambient condition. For instance, structure refinement has been made for (Mg,Fe)SiO3 post-bridgmanite at pressures above one megabar [166]; electron density distribution of -Ge has been determined at 12 GPa [102,370]. With the precise structural determination enabled by the multigrain approach, it is anticipated that many previously determined HP structures will be revisited with the technique.…”
Section: Hp Crystallographymentioning
confidence: 99%
See 3 more Smart Citations